Random Walk and Forward Exchange Rates: A Spectral Analysis - Upson, Roger B. (Journal of Financial and Quantitative Analysis, 1972)
This paper examines the random-walk hypothesis in the forward exchange market by applying spectral analysis to the three-month forward rates for dollars against sterling in the period 1961–1967.